Предмет: Алгебра,
автор: alemgul04
(х+5)(х-4)+х2+18=0
(х+7)(х-7)+(х-3)2=53
Ответы
Автор ответа:
0
(х+5)(х-4)+х2+18=0
1) раскроем скобки
(х+5)(х-4)+х2+18=0
х2 - 4х + 5х - 20 - х2 + 18 = 0
2) решаем
x2-x2 = 0
-20+18=-2
x2+x-20-x2+18=0
x-20+18=0
x-2=0
х=2
(х+7)(х-7)+(х-3)2=53
1) раскроем скобки
(х+5)(х-4)+х2+18=0
х2 - 4х + 5х - 20 - х2 + 18 = 0
2) решаем
x2-x2 = 0
-20+18=-2
x2+x-20-x2+18=0
x-20+18=0
x-2=0
х=2
(х+7)(х-7)+(х-3)2=53
(х^2-49)-(x^2-6x+9)=53
x^2-49-x^2+6x-9 = 53
6x= 53+9+496x=111
x= 111 : 6
х = 18.5
Похожие вопросы
Предмет: Русский язык,
автор: milanabezborodova10
Предмет: Геометрия,
автор: grebennikovaan26
Предмет: Українська мова,
автор: Аноним
Предмет: История,
автор: summer1974z
Предмет: История,
автор: ugrokbtapochkax